2021 30th IEEE International Conference on Robot &Amp; Human Interactive Communication (RO-MAN) 2021
DOI: 10.1109/ro-man50785.2021.9515356
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Design of a Robotic Mental Well-being Coach

Abstract: Recent research is emerging in the field of Social Robotics where robots have the potential to serve as tools to improve human well-being. However, research exploring the expectations and perceptions of prospective users of such robots, and the professionals who currently deliver these interventions, is limited. In this paper, we present qualitative analysis of discussions with prospective users and experienced coaches regarding the design of robot well-being coaches. We invited participants interested in well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…These findings provide further valuable evidence for the positive outcomes of employing a social robot as an intervention supporting people's well-being. Moreover, our results here add to previous studies [e.g., 33,42,105] that show the benefits of using robots for emotional support. Taken together with other results from this study (i.e., that people self-disclose increasingly more to a social robot over time and that people perceive a robot as more social over time), this study provides crucial evidence for establishing relationships with robots in health and care settings.…”
Section: Talking To Robots Positively Affects People's Well-beingsupporting
confidence: 84%
“…These findings provide further valuable evidence for the positive outcomes of employing a social robot as an intervention supporting people's well-being. Moreover, our results here add to previous studies [e.g., 33,42,105] that show the benefits of using robots for emotional support. Taken together with other results from this study (i.e., that people self-disclose increasingly more to a social robot over time and that people perceive a robot as more social over time), this study provides crucial evidence for establishing relationships with robots in health and care settings.…”
Section: Talking To Robots Positively Affects People's Well-beingsupporting
confidence: 84%
“…A study by Bodala and colleagues [47] employed a social robot delivering teleoperated mindfulness coaching for five weeks. Another example by Axelsson and colleagues [61] tested a robotic coach conducting positive psychology exercises, showing positive mood change after participation in the robotic intervention. Robotic interventions for people's wellbeing are rarely taking place in people's homes.…”
Section: Social Robots For Well Beingmentioning
confidence: 99%
“…Past works demonstrated that the human-like appearance of the robot influences the expectations of the users. For example, participants attributed human-like behaviors to humanoid robots, because they associated their shape with their functionalities [38]. On the other hand, the remaining papers in the review adopted a non-humanoid shape.…”
Section: A Recommendationsmentioning
confidence: 99%
“…On the other hand, the remaining papers in the review adopted a non-humanoid shape. In fact, a previous work [38] showed that participants who were asked to rank different robotic platforms (e.g., Jibo, Pepper, Miro) provided contradictory responses. Some of the participants preferred more humanoid robot shape, while other chose an abstract shape as the most suitable to be a robotic coach delivering wellbeing interventions.…”
Section: A Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation